Leveraging applications of formal methods, verification and validation. distributed systems : 8th International Symposium, ISoLA 2018, Limassol, Cyprus, November 5-9, 2018, Proceedings /: distributed systems : 8th International Symposium, ISoLA 2018, Limassol, Cyprus, November 5-9, 2018, Proceedings. Part III : (2018) - Unknown
No abstract available